A dynamic evacuation simulation framework based on geometric algebra. (September 2016) - Yu, Zhaoyuan; Wang, Jianjian; Luo, Wen; Hu, Yong; Yuan, Linwang; Lü, Guonian
Abstract: Integrating dynamic analysis models into geographic information system (GIS)-based evacuation simulations is important yet complex. Different models must be smoothly assembled according to the data processing flow to obtain a dynamic, data-forced evacuation simulation. However, because of the diversity of data types and dynamic data updating among different models, closely integrated evacuation simulations are complex and inefficient. In this study, geometric algebra (GA) is introduced to develop a dynamic evacuation simulation framework for a hazardous gas diffusion scheme. In the framework, geospatial data are first integrated into a unified virtual scene with different forms of multivector representation. The major simulation models of gas diffusion, risk assessment, and dynamic evacuation routing compose the major steps of the evacuation simulation. On the basis of the generalized multivector structure, dynamic exchange and updating geospatial data at different evacuation steps can be performed seamlessly with the multivector structure and GA operators. The framework is tested with a case study of a three-dimensional residential area, which shows that our framework can support the integration of dynamic evacuation processes and the model integration is direct and smooth. This framework may also provide a new solution for the integration and dynamic data updating in spatiotemporal GIS. Highlights: We designed a new dynamic evacuation framework using geometric algebra. Different geospatial data is unifiedly represented as a special form of multivector. Dynamical data change between different geospatial data/models is achieved. Analysis models of ESHGD are tightly integrated under this framework. A cases demonstrates that the ESHGD is constructed using the framework proposed.